Heat conduction in functionally graded solids - Chung, Ling Quan (2017)
The appearance of functionally graded materials has benefitted us over the years. Functionally graded solids, which are comprised of functionally graded materials, have varying properties across their spectrum. This allows researchers, engineers and people who are interested from various fields to come up with new and better products. Heat transfer is one of the many ways where the usefulness of functionally graded materials is being explored and pitted against other homogenous materials. By conducting a variety of analysis and case studies, we can come up with avenues where it was once not feasible with homogenous materials. In this report, heat transfer of functionally graded material will be analysed by numerical and mathematical approaches via the Boundary Element Method and MATLAB.